7y-9=y+3

Simple and best practice solution for 7y-9=y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-9=y+3 equation:


Simplifying
7y + -9 = y + 3

Reorder the terms:
-9 + 7y = y + 3

Reorder the terms:
-9 + 7y = 3 + y

Solving
-9 + 7y = 3 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-9 + 7y + -1y = 3 + y + -1y

Combine like terms: 7y + -1y = 6y
-9 + 6y = 3 + y + -1y

Combine like terms: y + -1y = 0
-9 + 6y = 3 + 0
-9 + 6y = 3

Add '9' to each side of the equation.
-9 + 9 + 6y = 3 + 9

Combine like terms: -9 + 9 = 0
0 + 6y = 3 + 9
6y = 3 + 9

Combine like terms: 3 + 9 = 12
6y = 12

Divide each side by '6'.
y = 2

Simplifying
y = 2

See similar equations:

| u(x)=-2x+1000 | | 30x-20/5 | | -92=-5v-7(v+8) | | Log(g)= | | (6+4x)=(4x-6) | | x-24=5x+6 | | xLog(n)= | | 5x^2-6x-100=0 | | (A^3/-2b)^2 | | (D^4-5d^2+4)y=0 | | 16x+3y-13x+14y= | | 4^7/4^2 | | z^4-iz^3+8z-8i=0 | | x-2/(2x^2)^2=0 | | 9x[x+1]=4 | | x^4-3x^3+7x^2+5x-9=0 | | (x-6)(x-3)=-2 | | a^2-8a=-16 | | 2(3x+6x)=25 | | 102/4 | | 105=-5(4b+7) | | (X+30)+(180-3x)+(1X)=180 | | 5v=11+3u | | 3-(-6x)=4x+9 | | 2cosx-4=0 | | f(a)=2a^2-16a+32 | | 2x(y-4)=2 | | 1/4(8x-20)=7 | | 2Z^2+4z-70=0 | | 16z+42=80 | | 2y+2x-3=0 | | X=-30+3x |

Equations solver categories